TEI Models for the Publication of Social Sciences and Humanities Journals: Opportunities, Challenges, and First Steps Toward a Standardized Workflow - Anne Baillot; Julie Giovacchini (Journal of the Text Encoding Initiative)
The TEI Guidelines are developed and curated by a community whose main purpose is to standardize the encoding of primary sources relevant for humanities research and teaching. But other communities are also working with TEI-based publication formats. The first goal of this paper is to raise awareness of the importance of TEI-based scholarly publishing as we know it today. The second goal is to contribute to a reflection on the development of a TEI customization that would cover the whole authoring-reviewing-publishing workflow and guarantee archiving options that are as solid for journal publications as what we now have for primary sources published in TEI.